Vitamin B12 status in rural adolescent school girls in Mysuru, India: A community-based cross-sectional study - K Jagadish Kumar; Sangeetha Balaji; Praveen Kulkarni; V G Manjunath; H R Nandish (Wolters Kluwer Medknow Publications, 2023)
Almost 56% of Indian adolescent girls aged 15-19 years suffer from anemia. Adolescent age is a period of many significant physiological changes that increase nutritional demand, and they remain at risk for nutritional deficiencies. Our aim is to assess the prevalence of Vitamin B12 deficiency among school-going adolescent girls aged 13-16 years of rural Mysore. This study was a cross-sectional study, conducted in two high schools in rural Mysuru. Adolescent girls aged 13-16 years were included. The chosen subjects underwent complete hemogram, peripheral smear examination, and vitamin B12 level estimation. Out of 98 subjects enrolled, 40.81% were found to be deficient in vitamin B12. Macrocytes and hyper-segmented neutrophils were found to have statistically significant (P value < 0.001) relationship with vitamin B12 deficiency. The relationship between vitamin B12 deficiency with either type of diet and anemia was statically insignificant (P > 0.05). The prevalence of vitamin B12 deficiency among rural adolescent girls in Mysuru is high. Other causes of nutritional anemia apart from iron deficiency, such as vitamin B12 deficiency, must be considered in the etiology of anemia and optimally treated. It is recommended to further strengthen the adolescent national health programs and food fortification programs.